Multi-objective optimization to the problem of distributing plant using genetic algorithms: preliminary issues for a proposed solution - Ruiz Lizama, Edgar Cruz (2014)
The article reviews the state of the art and theoretical concepts needed to develop a proposed solution to the Facility Layout Problem FLP. Article concepts such as meta heuristics, evolutionary computation, evolutionary programming, genetic algorithms, aimed to propose an alternative solution to the difficult problem of plant distribution are examined.